Smart thinking on co-creation and engagement: Searchlight on underground built heritage - Smaniotto Costa, C. (2023)
This paper aims to explore public participation for activating underground built heritage (UBH). It describes and analyses practices of stakeholders’ engagement in different UBH assets, based on experiences gathered in the scope of the European COST Action ‘Underground4value’. It brings together five inspiring cases from Italy, Portugal, Spain, Switzerland and the United Kingdom, in which digital and mobile technologies were used as tools to improve community experiences in UBH. Thus, the paper discusses ‘smartness’ from the perspective of people and communities around cultural assets, where ‘smartness’ becomes a new connotation and a pathway to advance (local) knowledge and know-how. Therefore, this paper takes on the challenge to define a smart city as an ecosystem for people’s empowerment and participation, and, in particular, to explore social tools for creating new values in heritage placemaking—where sharing knowledge becomes a fundamental principle.